Formulation and Evaluation of Sunscreen Gel Combination of Bisoctrizole and Gotu Kola Extract (Centella asiatica (L.) Urban) - Mardhiani, Yanni Dhiani; Supriadi, Dadih; Islamiyah, Putri Hafisa Nur (Indonesian Journal of Pharmaceutics, 2022)
Gotu kola extract has antioxidant activity and contains flavonoids that can absorb maximum wavelengths of UV radiation. Bisoctrizole is a photoprotective agent to minimize sun damage. The Sun Protection Factor value of sunscreen can be increased by combining Bisoctrizole and Gotu kola extract as sunscreen in the form of a gel. This study aims to develop a sunscreen gel from a combination of Bisoctrizole UV filter material and Gotu kola extract which has good physical properties and sun protection efficacy. Gel evaluation was carried out on organoleptic, homogeneity, adhesion, dispersion, viscosity, syneresis, pH, irritation test, stability test, and in vitro test of SPF value (UV-Visible Spectrophotometry). The results showed that the combination sunscreen gel (F5-F7) had excellent physical appearance and homogeneity, no syneresis, pH 4.96±0.01 - 5.30±0.01, viscosity 5960±106 - 9240±173 cps, spreadability 5.75±0.05 - 6.38±0.03 cm, adhesion 1.24±0.20 - 2.89±0.12 seconds, and is non-irritating. The results of the measurement of sunscreen activity showed that the SPF value of the Bisoctrizole 5% gel added with Gotu kola extract 5% (F5); 7.5% (F6); and 10% (F7), respectively, were 27.73±0.04; 34.56±0.23; and 37.31±0.36. There was a significant difference (p<0.05) in the room temperature gel stability test and the cycling test on pH, viscosity, and spreadability.. The highest SPF value was found in the gel combination of Bisoctrizole 5% with Gotu kola extract 10% (F7) with an increase of 55.58%. Gotu kola extract can be formulated with Bisoctrizole into a sunscreen gel with ultra photoprotective activity (SPF>15).